Merging Secret Sharing within Arabic Text Steganography for Practical Retrieval - Alaseri, Khaled Aydh; Gutub, Adnan Abdul-Aziz (IJRDO -Journal of Computer Science Engineering, 2018)
Secret sharing is becoming famous technique in cases where access to important resources has to be saved by many authorized persons. Steganography is another method used to hide information for personal usage whenever required.This paper improves modeling a steganography tool to hide shares generated from target access within texts, helping in the retrieval process. The work has built its model on an Arabic data set of Prophet Haddiths utilizing known Kashida Arabic text steganography, which is considered acceptable methods for hiding information. The suggested new approach merged the secret shares via steganography showing increase in capacity promising for research interesting direction of higher security.